Efektifitas Pemberian Tablet Fe dan Jus Pisang Ambon Dengan Tablet Fe Terhadap Kadar Hemoglobin - Sofia Mawaddah; Martha Noorjanah (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2022)
The most common nutritional problem in young women is iron deficiency or anemia. One way to prevent anemia is by consuming Ambon bananas by juicing them. The aim of this study was to determine the effectiveness of administering Fe tablets and Ambon banana juice with Fe tablets to hemoglobin levels in female students at SMPN 16 Petuk Ketimpun, Palangka Raya City. This research is a quantitative research with analytic observational method using Quasy Experiment research with a two group only-pre-post test design. The subjects of this study were 30 young women from SMP 16 Petuk Ketimpun, Palangka Raya City. The results of data analysis using the Wilcoxon test obtained a p value <0.05, i.e. p=0.001 which can be concluded that there was an effect of giving Fe tablets on increasing hemoglobin levels. = 0.000 which can be concluded that there is a significant effect between fe tablets and Ambon banana juice in increasing hemoglobin levels of female students